The Prophylactic Effect of Pinocembrin Against Doxorubicin-Induced Cardiotoxicity in an In Vitro H9c2 Cell Model - Sangweni, Nonhlakanipho F.; Moremane, Malebogo; Riedel, Sylvia; van Vuuren, Derick; Huisamen, Barbara; Mabasa, Lawrence; Barry, Reenen; Johnson, Rabia (Frontiers in Pharmacology, 2020)
Background: The chemotherapeutic use of Doxorubicin (Dox) has drastically decreased because of its dose-dependent cardiotoxic side effect. Numerous mechanisms, amongst them oxidative stress, mitochondrial depolarization and apoptosis have been identified to be at the forefront of Dox-induced cardiotoxicity. Flavonoids, such as pinocembrin, have been proposed to have therapeutic properties that could target some of these toxic effects. As such, we investigated the ability of pinocembrin (Pin) to attenuate Dox-induced cardiotoxicity in an in vitro H9c2 cardiomyoblast model. Methodology: To induce chronic cardiotoxicity, H9c2 cardiomyoblasts were treated with Dox (2μM) every second day for six days. The cells were also co-treated with pinocembrin (1μM) in order to assess the flavonoid’s cardioprotective potential as well as Dexrazoxane (20μM), which served as a positive control. Untreated cells served as a normal control. On day seven, we conducted biochemical analysis (ATP levels, oxidative stress, lipid peroxidation, antioxidant activity, mitochondrial potential and apoptosis) to assess the efficacy of pinocembrin. Results: Pinocembrin significantly attenuated Dox-induced oxidative stress and lipid peroxidation by increasing the activity of endogenous antioxidants such as superoxide dismutase and total glutathione content. Moreover, pinocembrin prevented Dox-induced loss in mitochondrial membrane potential (MMP), which led to an increase in cellular metabolic activity. Subsequently, pinocembrin was able to mitigate Dox-induced apoptosis by increasing the amount of viable cells as indicated by a significant reduction in apoptotic and necrotic cells. Conclusion: These findings demonstrate that pinocembrin attenuates the chronic cardiotoxicity inferred by Dox administration on the H9c2 cardiomyoblasts through its antioxidant and anti-apoptotic properties. We therefore, suggest that pinocembrin should be further investigated as a suitable candidate in the prevention of Doxorubicin-induced cardiomyopathy.